Aging of the endocrine system and its potential impact on sarcopenia - Vitale, Giovanni; Cesari, Matteo; Mari, Daniela (European journal of internal medicine, 2016)
Sarcopenia, occurring as a primary consequence of aging, is a progressive generalized decline of skeletal muscle mass, strength and function. The pathophysiology of sarcopenia is complex and multifactorial. One major cause of muscle mass and strength loss with aging appears to be the alteration in hormonal networks involved in the inflammatory processes, muscle regeneration and protein synthesis. This review describes the recent findings concerning the role of the aging on the endocrine system in the development of sarcopenia. We also report the benefits and safety of hormone replacement therapy in elderly subjects and discuss future perspectives in the therapy and prevention of skeletal muscle aging. •The aging of the endocrine system is implicated in the development of sarcopenia.•The risk/benefit ratio of androgen replacement therapy is unclear in frail elderly.•No benefit of oral DHEA supplementation has been demonstrated on muscle.•Targeting oxytocin receptor may represent a new therapeutic strategy for sarcopenia.